Fill the gap between public administration strategic management and plan man-agement. The italian PNRR and digital transition case - Aveni, Alessandro (Revista JRG de Estudos Acadêmicos, 2023)
The paper tries to clarify the gap between strategic management and plan management. This gap is not the only one in European and Italian plans. The research starts from the observation that co-governance between the central government and municipalities and local government failed in Italy so then the reforms and investment expected outcomes are at risk. The problem was detected when the author worked as a consultant in the last Italian resilience (PNRR) and digital (DTI) plans in 2022. To work together and have coordinated goals, PNRR and DTI must have a strategic control room and network governance very different from the one decided in 2019 (PNRR) and 2022 (revised DTI) and approved. The paper clarifies, using standard European tools, and using the case of DTI and its link with PNRR, the missed connections were essentially due to weak decisions, lack of methodology, and skilled people that put on risk the plans. The discussion doesn’t seek political implications and mistakes, it’s only an explanation of the risks due to the failure of technical skills and foresees implementation risks into the definition phase of the plans. The paper results in a suggestion for reformulation of the whole strategy and plan management process and new tools in Italian central and local public administration.